Anatomie d’une condamnation - Alessandro Gamberini (Laboratoire Italien)
The article aims at examining the judicial process that has led to the conviction of Adriano Sofri, Ovidio Bompressi and Giorgio Pietrostefani, for the murder of Commissioner Luigi Calabresi. After describing the conditions of the sentence given to the three former militants of “Lotta continua” and laying stress on some contradictory aspects in the informants’ statements on which the accusation is based, the author analyzes an internal contradiction in the way justice operates: a contradiction that has opposed, on many occasions during the long judicial process (from 1988 to 2000), the giudici di merito, who pronounce on the guilt of the defendants, and the giudici di legittimità, the judges of the court of Cassation, whose role is to guarantee the legitimacy of the procedures. The analysis of the different perspectives of both institutions helps to understand how the case was conducted: the “logical evidence” (that is to say, basically, a preconceived judgment on the historical and political sense of the case) has prevailed over the sheer absence of evidence.